Ультразвуковой контроль дефектов металлических изделий сложной формы; Дефектоскопия; № 5 - Ларионов В. В. Виталий Васильевич; Лидер А. М. Андрей Маркович; Долматов Д. О. Дмитрий Олегович; Седнев Д. А. Дмитрий Андреевич (2021, 2021)
Заглавие с экрана